Perceived involvement in health care decisions among US adults: Sociodemographic and medical condition correlates. Issue 6 (June 2021) - Langford, Aisha T.; Maayan, Eli; Lad, Meeki; Orellana, Kerli; Buderer, Nancy
Highlights: Secondary analysis of NCI's Health Information National Trends Survey (HINTS). Perceived involvement in decisions about health care was the primary outcome. Sociodemographic factors and 7 medical conditions were evaluated. Differences by race/ethnicity and educational attainment were observed. Abstract: Objective: To explore factors associated with how often US adults perceived that they were "always" involved in decisions about health care to the degree that they desired. Methods: We examined cross-sectional, nationally representative data from the 2018 Health Information National Trends Survey. There were 3504 responses in the full HINTS dataset; 2499 remained after eliminating respondents with missing data for any factor of interest. Sociodemographic factors included age, gender, race/ethnicity, and education. Medical conditions included diabetes, hypertension, heart disease, lung disease, arthritis, cancer, and depression. Participants were asked to think about communication with health professionals during the last 12 months and how often health professionals involved them in decisions about health care. Results: In univariate analyses, Asian and Hispanic race were associated with lower odds of always being involved in decisions about health care; whereas higher education and a history of cancer were associated with higher odds of "always" being involved in decisions about health care, p < 0.05. In multivariate analyses, race and education both remained significant; however, history of cancer did not. Conclusion: Differences by race/ethnicity and educational attainment exist regarding perceived involvement in decisions about health care. Practice implications: Findings may inform future shared decision making interventions.